FRI0500 INCIDENCE OF CLINICAL FRACTURES IN ADULTS WITH KIDNEY TRANSPLANT. (June 2019) - Rodríguez-Merlos, Pablo; Hernández, Yanielli; Napky, Gerardo; Leon, Lina; Navarro-Compán, Victoria; Lopez, Maria; Balsa, Alejandro; Jimenez, Carlos; Aguado, Pilar
Abstract : Background: Chronic kidney disease is associated with an increased risk of fractures. However, the existing evidence investigating the incidence of fractures after kidney transplant is scarce. Objectives: To evaluate the incidence of clinical fractures in patients with kidney transplant and analyze the possible factors that may influence its occurrence. Methods: A retrospective observational study of patients who underwent kidney transplant between 2005 and 2015 in a tertiary hospital was conducted. A minimum follow.up period of 6months after transplant was required. Sociodemographic and anthropometric data, clinical risk factors for bone fractures, drugs use (steroids, immunosuppressive drugs, vitamin D analogues, calcium and vitamin D supplements and calcimimetics), as well as biochemical and densitometric data to assess bone metabolism were retrieved from medical records. The occurrence of new clinical fractures after the transplant and throughout the follow-up period was recorded. The statistical analysis included univariable analysis using chi-square and Fisher's exact tests for the qualitative variables and T-Student and Mann-Whitney U for the quantitative variables. Subsequently, logistic regression multivariable analysis was carried out to investigate which factors were associated with fractures occurrence. Results: A total of 163 patients were included, 63 (38%) females, with a mean age of 51 ± 14.6 years. The etiology of kidney disease was polycystic kidney disease (24.2%), glomerulonephritis (23.6%), diabetes mellitus (5.5%), vasculopathy (5.5%), connective tissue disorders (2.4%) and miscellany (38.7%). The daily average dose of steroids one year after transplant was 5.8 ± 4.4 mg. Bone densitometry was performed before transplant in 27 patients (19.6%), ten of whom (37%) presented osteopenia and 7 (26%) osteoporosis. The ten-year probability of bone fracture risk (FRAX) before transplant was 2.6 ± 2.6. Mean follow-up after transplant was 8.7 ± 3.5 years. During this period, 23 (13.9%) patients suffered a clinical fracture, with an average time of appearance after transplant of 5.5 ± 3.3 years. These were located in hip (6 - 26.1%), vertebrae (2- 8.7%), extremities (9 – 39.1%) and hands and feet (6 – 26%). One year after transplant, 65.6% had vitamin D deficiency (<30 ng/dl serum calcidiol leves) and 12.2% had levels compatible with osteomalacic range (<10ng/dl). The data of the descriptive study stratified by the fracture occurrence are shown in Table 1 . Compared with the subgroup patients without (Fx -), patients with (Fx +) post-transplant fractures showed to be more frequely female (60.9% vs 34.5%, p=0.01), older (50.1 ± 14.6 vs 56.3 ± 14.1 p=0.03), had more pre-transplant major clinical FRAX ((2.4 ± 1.9 vs 4 ± 4.7, p=0.03), and higher levels of PTH (98.2 ± 75.7 vs 140.1 ± 86.9 p=0.02) and serum alkaline phosphatase [ALP] (90.2 ± 37 vs 117.8 ± 60.4, p=0.02) after one year of transplant. Also, a trend to present a higher prevalence of pre-transplant clinical fractures was observed in the second group (5.6% vs 17.4%, p=0, 06). No difference in the use of immunosupressants were detected. The multivariable analysis showed a significant association between post-transplant fractures and female gender (OR of 3.8, p=0.03) and higher levels of ALP (OR of 1.01, p=0.03). Conclusion: In patients with kidney transplant, an incidence of clinical fracture of 13.9% is observed after a mean follow-up of 8.7 year. The female population seems especially susceptible to present fractures. The persistence of a possible pre-transplant autonomous secondary hyperparathyroidism one year after kidney transplant seems to influence the risk of fracture. Disclosure of Interests: Pablo Rodríguez-Merlos: None declared, Yanielli Hernández: None declared, Gerardo Napky: None declared, Lina Leon: None declared, Victoria Navarro-Compán: None declared, Maria Lopez: None declared, Alejandro Balsa Grant/research support from: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Consultant for: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Sandoz, Lilly, Paid instructor for: Pfizer, Speakers bureau: Pfizer, Novartis, UCB, Nordic, Sanofi, Sandoz, Lilly, Carlos Jimenez: None declared, Pilar Aguado: None declared